The labour theory of value - Dooley, Peter C. (Routledge frontiers of political economy ;, 2005)
Exploring the origins and development of the labour theory of value, Peter Dooley examines its emergence from the natural law philosopher of the sixteenth and seventeenth century and its domination of the classical school of economics. This book will prove to be essential reading for all students of the history of economics.